2017
DOI: 10.1007/jhep01(2017)089
|View full text |Cite
|
Sign up to set email alerts
|

2D quantum gravity on compact Riemann surfaces with non-conformal matter

Abstract: Abstract:We study the gravitational action induced by coupling two-dimensional nonconformal, massive matter to gravity on a compact Riemann surface. We express this gravitational action in terms of finite and well-defined quantities for any value of the mass. A small-mass expansion gives back the Liouville action in the massless limit, the Mabuchi and Aubin-Yau actions to first order, as well as an infinite series of higher-order contributions written in terms of purely geometric quantities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…[6] has studied the metric dependence of the partition function of non-conformal massive matter on compact Riemann surfaces and shown that a gravitational action defined by (1.1) contains these Mabuchi and Aubin-Yau actions as first-order corrections (first order in m 2 A where m is the mass and A the area of the Riemann surface) to the Liouville action. The study of [6] was further confirmed and generalized in [7] where an exact formula for the gravitational action for any value of the mass was obtained, its expansion in m 2 A giving back the results of [6]. The Mabuchi action has drawn much attention in recent years.…”
Section: Jhep11(2017)154mentioning
confidence: 75%
See 4 more Smart Citations
“…[6] has studied the metric dependence of the partition function of non-conformal massive matter on compact Riemann surfaces and shown that a gravitational action defined by (1.1) contains these Mabuchi and Aubin-Yau actions as first-order corrections (first order in m 2 A where m is the mass and A the area of the Riemann surface) to the Liouville action. The study of [6] was further confirmed and generalized in [7] where an exact formula for the gravitational action for any value of the mass was obtained, its expansion in m 2 A giving back the results of [6]. The Mabuchi action has drawn much attention in recent years.…”
Section: Jhep11(2017)154mentioning
confidence: 75%
“…As noted before, δλ 0 = 0 and, hence, there is no zero-mode contribution to the second term and one could just equally well rewrite the following results in terms of the ζ-functions defined by excluding the zero-mode [7]. Here, however, this is not of particular interest to us, and thus…”
Section: Variation Of the Determinantmentioning
confidence: 84%
See 3 more Smart Citations